Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.